Enhancing the learning of technology in early childhood settings. Issue 1 (March 2019) - Fox-Turnbull, Wendy
This article describes a study of early childhood teachers' understanding of teaching and learning in children 4 and 5 years of age in technology education. The research aimed at assisting teachers' understanding of learning in technology using a developed framework. This study investigated the development of dispositions and attitudes including the building of children's confidence and self-belief in their capabilities, within four aspects of learning and across five predetermined behaviours relevant to technology education. The study employed qualitative research methods to assist teachers with the use of an observation and conversation framework aimed to improve their ability to assess formatively their children and their own ability to give specific feedback. Observations and interviews were used to gauge teachers' developed understandings of children's learning in technology. The study shows that the framework used benefitted teachers and children. It allowed for insight into understanding how and what children learn in technology and teachers' understanding of technology.